2012
DOI: 10.1002/ptr.4779
|View full text |Cite
|
Sign up to set email alerts
|

Lupenone Isolated from Adenophora triphylla var. japonica Extract Inhibits Adipogenic Differentiation through the Downregulation of PPARγ in 3T3‐L1 Cells

Abstract: Adenophora triphylla var. japonica (Campanulaceae) is known to have anti-inflammatory and anti-tussive effects. Dysfunction of adipocytes and adipose tissue in obesity is related to various inflammatory cytokines or adipokines. In this study, we investigated whether lupenone isolated from A. triphylla var. japonica extract inhibits adipocyte differentiation and expression of adipogenic marker genes in 3T3-L1 preadipocytes. We demonstrated that lupenone resulted in a significant reduction in lipid accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 27 publications
0
33
0
1
Order By: Relevance
“…Ba-jiao is a perennial herb, and when we measured the largest part of fresh Rhizoma Musae using a standard ruler, the obtained size (diameter) was used to represent the growth stage. The different growth stages (5,7,10,13,15, and 20 cm) of Rhizoma Musae collected at the same harvest time and origin displayed a range of lupenone and β-sitosterol levels. When the diameter of Rhizoma Musae was approximately 7-13 cm, lupenone content was higher.…”
Section: Quantitative Determination Of Lupenone and β-Sitosterol In Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Ba-jiao is a perennial herb, and when we measured the largest part of fresh Rhizoma Musae using a standard ruler, the obtained size (diameter) was used to represent the growth stage. The different growth stages (5,7,10,13,15, and 20 cm) of Rhizoma Musae collected at the same harvest time and origin displayed a range of lupenone and β-sitosterol levels. When the diameter of Rhizoma Musae was approximately 7-13 cm, lupenone content was higher.…”
Section: Quantitative Determination Of Lupenone and β-Sitosterol In Rmentioning
confidence: 99%
“…Current studies have shown that lupenone and β-sitosterol possess multiple pharmacological activities. For example, in vitro studies have found that lupenone stimulates melanogenesis in B 16 murine melanoma cells [10], as well as inhibits α-glucosidase (α-Glu) and protein tyrosine phosphatase 1B (PTP1B) activities [11,12], Furthermore, lupenone inhibits adipogenic differentiation via downregulation of peroxisome proliferator-activated receptor PPARγ expression in 3T3-L1 cells [13]. Additionally, previous studies have reported that β-sitosterol inhibits the growth of HT-29 human colon cancer cells and induces apoptosis of LNCaP human prostate cancer cells in vitro [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Lupenone (3) inhibits adipocyte differentiation by suppressing PPARγ and C/EBPα protein levels (Ahn and Oh, 2013). It also increases the tyrosinase enzyme expression via mitogen-activated protein kinase phosphorylated extracellular signal regulated kinases 1 and 2 phosphorylation inhibition which results to stimulation of melanogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…마시거나 즙을 내어 먹은 것으로 확인되었다 (Kim and Kang, 2016). Konno et al, 1981;Jiang and Gao, 1990;Kuang et al, 1991;Moon et al, 1999;Asano et al, 2000;Yao et al, 2007;Koike et al, 2010;Ahn, 2013;Kang et al, 2013a;Yoon et al, 2015). Chang et al, 1986;Liu et al, 1988;Wang et al, 1988;Lee and Kim, 1989;Lee and Seo, 1990;Lee and Ko, 1992;Zhu et al, 2001;Yoo et al, 2002;Thuy et al, 2003;Qing et al, 2006;Yuan and Liang, 2006;Liang et al, 2007;Ushijima et al, 2008;Xu et al, 2008;Ichikawa et al, 2009;Zhang et al, 2009;Liu et al, 2010;Qi et al, 2011;Wakana et al, 2011;Wang et al, 2011b;Hu et al, 2012;Ren et al, 2013;Wakana et al, 2013;Zhao et al, 2013;He et al, 2014).…”
mentioning
confidence: 99%